ISOLASI DAN IDENTIFIKASI SENYAWA ANTIMAKAN DARI BATANG TUMBUHAN BROTOWALI (Tinospora tuberculata BEUMEE.) - Sukadana, I M.; Susanah Rita, Wiwik; R. Koreh, Frida (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification of antifeedant compounds from brotowali stem (Tinospora tuberculata BEUMEE.) was done. Brotowali dry powder of 1 kg was extracted using methanol by maceration, The methanol extract then was fractionated repeatedly by n-hexane, so that methanol and n-hexane extracts were obtained. Both of extracts were evaporated by rotary vacuum evaporator, so concentrated methanol and n-hexane extracts were obtained and then their antifeedant activity was tested. More active extract was separated by thin layer chromatography (TLC) then continued by column chromatography utilizes silica gel 60 as a stationary phase and the best mobile phases of TLC. Fractions obtained were tested of their antifeedant activity. More active fraction then was tested its purity and identified by phytochemical test and UV-vis and infrared spectrophotometer. As much as 97.07 g of concentrated methanol extract was resulted from 1 kg brotowali dry powder. Fractionation of the methanol extract using n-hexane resulted 22.92 g of concentrated methanol and 21.71 g of concentrated n-hexane. n-hexane extract points out more activity as antifeedant than methanol extract. The best mobile phase of TLC was n-hexane: chloroform (1:1 ). The unite result from the column chromatography was obtained 3 fractions where fraction c points out antifeedant active. The purity test of fraction c was obtained 1 spot so continued by phytochemical test and UV-vis and infrared spectrophotometer. Phytochemical test and spectrophotometry analysis from active isolate (fraction c) point out that the compound included triterpenoid group that absorb on wavelength 288.6 nm and 310.6 nm, and be considered having functional group of O-H bonded, CO, C-H, C=O, C=C, and C-H.
Keywords: Brotowali, Tinospora tuberculata BEUMEE, Antifeedant